Effects of Simulated Microgravity on Ultrastructure and Apoptosis of Choroidal Vascular Endothelial Cells - Zhao, Hongwei; Shi, Yuanyuan; Qiu, Changyu; Zhao, Jun; Gong, Yubo; Nie, Chuang; Wu, Bin; Yang, Yanyan; Wang, Fei; Luo, Ling (Frontiers in Physiology, 2021)
Background It was confirmed that simulated microgravity (SMG) led to ultrastructural alterations and apoptosis in many types of microvascular endothelial cells. However, whether SMG would also affect choroidal vascular endothelial cells (CVECs) remains unknown. This study was designed to investigate the effects of SMG on ultrastructure and apoptosis of CVECs. Methods The rotary cell culture system (RCCS) was utilized to simulate microgravity condition. Human CVECs were cultured under normal gravity (NG) or SMG condition for 3 days. The ultrastructure was viewed under transmission electron microscopy, and the organization of F-actin was observed by immunofluorescence staining. Additionally, the apoptosis percentage was calculated using flow cytometry. Moreover, the mRNA and protein expression of BAX, Bcl-2, Caspase3, Cytochrome C, p-AKT, and p-PI3K were detected with quantitative PCR and Western blot at different exposure time. Results In the SMG group, CVECs presented with a shrunk cell body, chromatin condensation and margination, mitochondria vacuolization, and apoptotic bodies. The amount of F-actin decreased, and the filaments of F-actin were sparse or even partly discontinuous after cultivation under SMG for 72 h. The proportions of apoptotic CVECs in SMG groups at 24 and 72 h were significantly higher than those in the NG group (P < 0.001). The mRNA and protein expression of Bax, Caspase3, and Cytochrome C of CVECs in SMG groups at 24 and 72 h significantly increased than those of the NG group, respectively (P < 0.001). The alterations of p-AKT and p-PI3K protein expression possessed similar trends. On the contrary, the mRNA and protein expression of Bcl-2 in CVECs under SMG at 24 and 72 h were significantly less than that of the NG group, respectively (P < 0.001). Conclusion Simulated microgravity conditions can lead the alterations of the F-actin structure and apoptosis of CVECs. The Bcl-2 apoptosis pathway and PI3K/AKT pathway may participate in the damage of CVECs caused by SMG.